Comparing the diagnostic value of 18F-FDG PET/CT scan and bone marrow biopsy in newly diagnosed pediatric neuroblastoma and ganglioneuroblastoma - Fu, Zheng; Ren, Jiazhong; Zhou, Jing; Shen, Junkang (Frontiers in Oncology, 2022)
Objective: To compare the diagnostic value of 18F-fluorodeoxyglucose (18-FDG) positron emission tomography (PET)/computed tomography (CT) (18F-FDG PET/CT) scan and bone marrow biopsy (BMB) for evaluating bone marrow infiltration (BMI) in newly diagnosed pediatric neuroblastoma (NB) and ganglioneuroblastoma (GNB). Methods: We retrospectively reviewed 51 patients with newly diagnosed NB and GNB between June 1, 2019, and May 31, 2022. Each patient had undergone 18F-FDG PET/CT and BMB within one week and received no treatment. Clinical data were collected and statistically analyzed, including age, sex, pathologic type, and laboratory parameters. 18F-FDG PET/CT and BMB revealed the result of bone lesions. Results: Concordance analysis showed that, in this study population, 18F-FDG PET/CT and BMB were in moderate agreement (Cohen’s Kappa = 0.444; p = 0.001), with an absolute agreement consistency of 72.5% (37 of 51). The analysis of receiver operating characteristic (ROC) curve determined that the areas under the ROC curve (AUCs) of SUVBM and SUV/HE-SUVmax were 0.971 (95% CI: 0.911–1.000; p < 0.001) and 0.917 (95% CI: 0.715–1.000; p < 0.001) to predict bone-bone marrow involvement (BMI), respectively. Conclusion: 18F-FDG PET/CT detects BMI with good diagnostic accuracy and can reduce unnecessary invasive inspections in newly diagnosed pediatric NB and GNB, especially patterns C and D. The analysis of the semi-quantitative uptake of 18F-FDG, including SUVBM and SUVBM/HE-SUVmax, enables an effective differentiation between patterns A and B.